The Analysis of Workload and Safety Communication Against Burnout Syndrome in Inpatient Nurses (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Burnout is a psychological problem that attacks nurses and is one of the risks causes nursesto do unsafe actions. Nurses suffering from burnout and have a less safe environment will implementinefficient care systems. Generally, high workload is directly proportional to the incident of burnout. Thisresearch study aimed to find the effect of workload and safety communication on the level of burnout ininpatient nurse services.Method: This research was a cross-sectional study implemented at Rumah Sakit Umum Haji and Rumahsakit Islam Jemursari Surabaya, Indonesia. This implementation of research study was started in April toJune 2019. The samples were collected using two populations of sampling method and got 138 nurses assamples. To analyze the effect of workload and safety communication on burnout syndrome, the researcherused multinomial logistics.Results: The results of Multinomial logistic test showed that workload affected the incidence of burnoutwith a value of p = 0.037 and safety communication did not affect the incidence of burnout syndrome witha value of p = 0.274.Conclusion: Workload affected the burnout syndrome incidence, while safety communication had nonotable effect on burnout syndrome. The researcher suggests the hospitals to provide mental and physicalhealth services, as well as stress coping training for nurses.
Keywords: Workload, Safety communication, Burnout